A method for evaluating operational implications of regulatory constraints on Arctic shipping. (January 2022) - Browne, Thomas; Tran, Trung Tien; Veitch, Brian; Smith, Doug; Khan, Faisal; Taylor, Rocky
Abstract: Development of effective marine policy necessitates evidence-based, data-driven evaluations of the effects of regulatory constraints on operations. This is essential to better understand implications of policy decisions on complex socio-technical systems. This paper demonstrates a generalized methodology for evaluating operational implications associated with implementing maritime regulations. The method combines a ship performance model, regulatory constraint models, and multi-criteria pathfinding and optimization algorithms to evaluate and compare the operational implications of different regulatory constraints. The method is applied to Arctic shipping. The Polar Operational Limit Assessment Risk Indexing System (POLARIS) and the Arctic Ice Regimes Shipping System (AIRSS) are considered. POLARIS and AIRSS are regulatory guidelines used to assign structural safety constraints on ships in ice. Four approaches for assigning structural safety constraints are modelled: 1) POLARIS, 2) AIRSS, 3) speed limits established through a first-principles ship-ice interaction model, and 4) navigation in the absence of structural safety constraints. Operational implications are measured as distance, voyage time, and fuel consumption. Route optimization is validated against expert opinion of Arctic ship captains. Results indicate AIRSS is the more conservative regulatory guideline, yet associated with decreased voyage time and fuel consumption. Implications for marine policy and safe navigation are that, while POLARIS offers flexibility to operate in more severe ice conditions, it increases voyage time, fuel consumption, and the risk of vessel damage. Competent Arctic seafarers are critical for safe and efficient operations. The generalized methodology provides marine policy-makers and industry stakeholders with a means to evaluate operational implications of maritime regulations. Highlights: A generalized methodology to evaluate the operational implications associated with implementing maritime regulations. The methodology combines a ship performance model, regulatory constraints, and multi-criteria pathfinding and optimization. Case study: Operational implications of POLARIS and AIRSS regulatory guidelines for a PC5 vessel navigating the NWP. POLARIS allows operation in more severe ice regimes, increasing voyage time, fuel consumption, and risk of vessel damage. AIRSS is the more conservative regulatory guideline, yet associated with decreased voyage time and fuel consumption.